Feasibility of the environmentally friendly TPSS location selection zone in RT.08, Rorotan Village - Debby Syafriyandi; Arfilian Permana Putra; Surya Kurniawan; Wa Ode Nurhaidar; Rosdiana Trialita; Sandrina Hadi Rabbani; Muhammad Syaiful Nurohman; Desty Aulia Maharani (PT WIM Solusi Prima, 2026)
This study was conducted to analyse the suitability of the Temporary Waste Management Site (TPSS) location for the appropriate zone based on population, density, and land area in RT 008, Rorotan Village, Cilincing District, North Jakarta. The purpose of this study was to evaluate the suitability of the current TPSS location and to provide data-based recommendations for a more environmentally friendly site that meets community needs. The methodology used was descriptive quantitative with a direct interview approach with 30 randomly selected respondents. Data were analysed by categorising respondents' answers into three groups: agree, disagree, and neutral regarding the suitability of the TPSS location. The results showed a varied distribution of opinions: 43% of respondents agreed because the location is far from residential areas and its cleanliness is maintained; 37% disagreed because of air pollution and the cramped location; and 20% were neutral. The main conclusion is that the TPSS location in RT 008 is highly unsuitable, as it could cause environmental pollution and health problems. This study recommends constructing a wall to reduce unpleasant odours and expanding the TPSS area to accommodate the increasing volume of waste.